Diagnosis and Treatment of Vulvo-Perineal Endometriosis: A Systematic Review - Maillard, Charlotte; Cherif Alami, Zineb; Squifflet, Jean-Luc; Luyckx, Mathieu; Jadoul, Pascale; Thomas, Viju; Wyns, Christine (Frontiers in Surgery, 2021)
Objective: To describe the available knowledge on vulvo-perineal endometriosis including its diagnosis, clinical management and recurrence rate. Methods: We followed the PRISMA guidelines for Systematic Reviews and our study was prospectively registered with PROSPERO (CRD42020202441). The terms “Endometriosis” and “Perineum” or “Vulva” were used as keywords. Cochrane Library, Medline/Pubmed, Embase and Clinicaltrials.gov were searched. Papers in English, Spanish, Portuguese, French or Italian from inception to July 30, 2020 were considered. Reference lists of included articles and other literature source such as Google Scholar were also manually scrutinized in order to identify other relevant studies. Two independent reviewers screened potentially eligible studies according to inclusion criteria. Results: Out of 539 reports, 90 studies were eligible including a total of 283 patients. Their mean age was 32.7 ± 7.6 years. Two hundred sixty-three (95.3%) presenting with vulvo-perineal endometriosis have undergone either episiotomy, perineal trauma or vaginal injury or surgery. Only 13 patients (4.7%) developed vulvo-vaginal endometriosis spontaneously i.e., without any apparent condition favoring it. The reasons that motivated the patients to take medical advice were vulvo-perineal cyclical pain increasing during menstruations (98.2% of the patients, n = 278). Out of the 281 patients for whom a clinical examination was described, 274 patients (97.5%) showed a vulvo-perineal nodule, mass or swelling while six presented with bluish cutaneous lesions (2.1%) and 1 with bilateral polyps of the labia minora (0.4%). All but one patients underwent surgical excision of their lesions but only 88 patients (28.1%) received additional hormonal therapy. The recurrence rate was 10.2% (29 patients) considering a median follow-up period of 10 months (based on 61 studies). Conclusion: In conclusion, vulvo-perineal endometriosis is a rare entity with approximately 300 cases reported in the literature since 1923. With the available knowledge shown in this systematic review, we encourage all practitioners to think about perineal endometriosis in case of perineal cyclical pain with or without previous perineal damage. Diagnosis should be done with clinical exam, perineal ultrasound and pelvic MRI when available. In case of anal sphincter involvement, perianal ultrasound should be performed. Surgical excision of the lesion should be realized in order to remove the lesion and to confirm the diagnosis histologically. Hormonal treatment could be proposed to attempt to decrease the size of a large lesion before surgery or to avoid recurrence of the lesion. As evidence-based approach to the diagnosis, treatment and recurrence rate of affected patients remains a challenge given its low prevalence, the variations in management found in the articles included and the limited quality of available studies, we suggest that a prospective database on vulvo-perineal endometriosis should be generated to increase knowledge but also awareness among healthcare professionals and optimize patients' care. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/, identifier: CRD42020202441.